Ketaksaan Makna Dalam Acara Waktu Indonesia Bercanda - Fatmawati Usman; Dakia N. Djou; Ulfa Zakaria (PT PUSTAKA CENDEKIA GROUP, 2026)
This study aims to describe: (1) the types of ambiguity in meaning in the program Waktu Indonesia Bercanda and (2) the semantic relations found in the program. The approach used in this research is a semantic approach with a descriptive qualitative method. The data collection techniques were carried out by searching for and downloading videos, watching and observing the broadcasts, identifying the data, and recording instances that contain ambiguity of meaning. The data analysis techniques included identifying the data, classifying the recorded data, analyzing the data based on Ullmann’s semantic theory, and drawing conclusions from the analysis results. Based on the research findings, it was discovered that there are 21 instances of ambiguity in meaning in the program Waktu Indonesia Bercanda, which fall into three main categories: 3 phonetic ambiguities, 7 grammatical ambiguities, and 11 lexical ambiguities. In addition, this study also shows the presence of semantic relations in the utterances within the program, including 6 cases of synonymy, 3 cases of antonymy, 5 cases of polysemy, and 2 cases of ambiguity. In conclusion, ambiguity arises when a word, phrase, or sentence has more than one possible interpretation, leading to differences in understanding between the speaker and the listener.